PROBLEMS AND PROSPECTS OF ORGANIZING TEA PRODUCTION CLUSTERS IN UZBEKISTAN - D. Isroilova (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article analyzes the conditions for the establishment of tea production clusters in our country, and gives effective proposals for the establishment of clusters.